Penser les ambitions singulière et plurielle dans un atelier de philosophie. L’amor mundi d’Arendt - Lara Pierquin-Rifflet (Éducation et Socialisation)
This article proposes to question the relevance and fruitfulness of (re)reading the work of Hannah Arendt in the context of the practices of Philosophy for Children (P4C), in particular with regard to the problematic articulation of singular and plural issues, hindering their political ambition. Generally speaking, Arendt's work is mobilized as much by the opponents as by the defenders of the P4C. Firstly, we will examine three positions which challenge the P4C based on Arendt. This will make it possible to highlight, secondly, three central problems in education and training, and to show how these could be re-examined via Arendtian paradoxology (Tassin, 2018, p. 172). Thirdly, an attempt will be made to reconstruct the political anthropology that Arendt aimed for around amor mundi (love of the world), with a view to proposing a translation into a P4C analysis grid, in school contexts of primary classes (France and Belgium). It is not so much a question of thinking “in the way of” Arendt, as of taking paths that she opened.